Menghitung Hasil Estimasi Sumberdaya Nikel Laterit Menggunakan Metode Ordinary Kriging (OK) - jenius, (ReTII, 2021)
Nickel laterites make up 60 to 70% of the world's Ni resources, but even though they have been mined for approx 140 years, until 2000 they accounted for less than 40% of global Ni production, the remainder is from sulfide ores. Laterite nickel deposits are formed by prolonged and pervasive weathering of ultramafic rocks containing Ni silicates, generally in tropical to subtropical climates. The deposits can be further classified as hydro silicate deposits, clay silicate deposits, and oxide deposits based on the mineralogy of the ore. The physical and chemical properties of laterite nickel deposits are a function of many factors, including the composition of the host rock. This research is divided into several stages, namely: field data collection (drill data), data from this stage is used to determine the depth and distribution of the laterite zone. Perform laboratory analysis to obtain Ni levels. As well as Performing Modeling to determine the distribution model of the elements in nickel deposits based on laboratory analysis data, the method used in this study is themethod Ordinary Kriging (OK).